Antibacterial, antibiofilm, and anti-adhesion activities of Piper betle leaf extract against Avian pathogenic Escherichia coli - Kulnanan, Pawinee (2022)
Piper betle leaves have traditionally been used to treat many diseases, including bacterial infections. The present studyaimed to investigate the antibacterial, antibiofilm, and anti-adhesion activities of P. betle extract against avian pathogenicEscherichia coli (APEC). The ethanol extract of P. betle leaves demonstrated strong antibacterial activity against clinicalisolates of APEC with MIC and MBC values ranging from 0.5 to 1.0 mg/mL as compared with 1% DMSO, a negative control.Disruption and breakdown of the bacterial cells were detected when the cells were challenged with the extract at 2 × MIC.Bacterial cells treated with the extract demonstrated longer cells without a septum, compared to the control. The extract at1/8, 1/4, and 1/2× MIC significantly inhibited the formation of the bacterial biofilm of all the tested isolates except the iso-late CH10 (P < 0.05) without inhibiting growth. At 1/2 × MIC, 55% of the biofilm inhibition was detected in APEC CH09,a strong biofilm producer. At 32 × MIC, 88% of the inhibition of viable cells embedded in the mature biofilm was detectedin APEC CH09. Reduction in the bacterial adhesion to surfaces was shown when APEC were treated with sub-MICs of theextract as observed by SEM. Hydroxychavicol was found to be the major compound presented in the leaf extract as detectedby GC–MS analysis. The information suggested potential medicinal benefits of P. betle extract to inhibit the growth, biofilm,and adhesion of avian pathogenic E. coli.